The effect of lipid peroxidation products on reactive oxygen species formation and nitric oxide production in lipopolysaccharide-stimulated RAW 264.7 macrophages - Ambrožová, Gabriela; Pekarová, Michaela; Lojek, Antonín (Toxicology in vitro, 2011)
Lipid peroxidation induced by oxidants leads to the formation of highly reactive metabolites. These can affect various immune functions, including reactive oxygen species (ROS) and nitric oxide (NO) production. The aim of the present study was to investigate the effects of lipid peroxidation products (LPPs) - acrolein, 4-hydroxynonenal, and malondialdehyde - on ROS and NO production in RAW 264.7 macrophages and to compare these effects with the cytotoxic properties of LPPs. Macrophages were stimulated with lipopolysaccharide (0.1 μg/ml) and treated with selected LPPs (concentration range: 0.1-100 μM). ATP test, luminol-enhanced chemiluminescence, Griess reaction, Western blotting analysis, amperometric and total peroxyl radical-trapping antioxidant parameter assay were used for determining the LPPs cytotoxicity, ROS and NO production, inducible nitric oxide synthase expression, NO scavenging, and antioxidant properties of LPPs, respectively. Our study shows that the cytotoxic action of acrolein and 4-hydroxynonenal works in a dose- and time-dependent manner. Further, our results imply that acrolein, 4-hydroxynonenal, and malondialdehyde can inhibit, to a different degree, ROS and NO production in stimulated macrophages, partially independently of their toxic effect. Also, changes in enzymatic pathways (especially NADPH-oxidase and nitric oxide synthase inhibition) and NO scavenging properties are included in the downregulation of reactive species formation.
Keywords: Nitric Oxide; down regulace; Cell Line, Transformed; transformované buněčné linie; viabilita buněk; Lipopolysaccharides; dusitany; akrolein; reaktivní formy kyslíku; NADPH Oxidases; NADPH-oxidasy; lipopolysacharidy; Nitrites; Nitric Oxide Synthase Type II; Cell Survival; oxid dusnatý; Aldehydes; Macrophage Activation; aktivace makrofágů; Malondialdehyde; osmolární koncentrace; aldehydy; Reactive Oxygen Species; Time Factors; Acrolein; Animals; Down-Regulation; zvířata; makrofágy; malondialdehyd; časové faktory; Free Radical Scavengers; Osmolar Concentration; myši; peroxidace lipidů; synthasa oxidu dusnatého, typ II; Lipid Peroxidation; Mice; Macrophages; scavengery volných radikálů